A re‐audit of cervical screening uptake in a dermatology cohort on immunosuppressive medications. (5th July 2018) - Nic Dhonncha, E.; Callanan, I.; Clowry, J.; Collins, P.; Moriarty, B.; Kirby, B.; Lally, A.
Abstract : Linked Article:  Clowry et al. Br J Dermatol 2018;172 :1682–3 .